(3JMaI GdCdHGH deLGdSI GdCMHGHs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW,J (B718 (3g` s ((3eMeO Hf GHQGgje GdYjfJGHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdYGde Ydi JhMjOg aTgO cd ehLhO HhLhOg CeG HYO aEf Gdgd JYGdi MdJ bOQJg s
(3BNQgG (B:s
(3gPG eG GfJgi Edjg heG GfJbGg eMeO Hf YGUe ef GdcJGH GdeSei efGgL GdacQ heHGgL GdYHQ hSeGg JMaI GdCdHGH s
(3jdjg fbhd ef cJH eJaQbI ai GdJGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B143s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs